Interruptions of antiretroviral therapy in children and adolescents with HIV infection in clinical practice: a retrospective cohort study in the USA. Issue 1 (27th October 2016) - Rakhmanina, Natella; Lam, Kam S; Hern, Jaclyn; Young, Heather A; Walters, Alex; Castel, Amanda D
Abstract : Introduction: Changes in combination antiretroviral therapy (cART) throughout childhood challenge the continuity of paediatric HIV treatment. This study aimed to evaluate the prevalence of treatment interruption (TI), including lamivudine (3TC) monotherapy, and the relationship of TI to virologic and immunologic parameters in HIV‐infected paediatric patients. Methods: Nested within a prospective observational study of a city‐wide cohort of HIV‐infected persons in the District of Columbia, this sub‐study collected retrospective data on antiretroviral therapy, enrolment (endpoint) and historic (lifelong) CD4 counts and HIV RNA viral load (VL) of the paediatric cohort. TI was defined as interruption of cART ≥4 consecutive weeks. Data on TI, including 3TC monotherapy TI (MTI), were collected. Descriptive statistics and univariate testing were used to compare children with TI and MTI to children on continuous treatment (CT). Results: Thirty‐eight (28%) out of 136 enrolled children (median age=12.9 years) experienced TI, with 14 (37%) of those placed on 3TC MTI. Significantly lower endpoint median CD4 counts (598 cells/mm 3 vs. 815 cells/mm 3 ; p= 0.003) and CD4% (27.5% vs. 33%; p =0.006) were observed in the TI cohort as compared to the CT cohort. The median endpoint VL in the overall TI cohort was ~4 times higher than among the CT cohort (1427 copies/mL vs. 5581 copies/mL; p <0.0001). After a median TI duration of one year, a majority ( n =31; 82%) of patients with TI restarted cART, including 100% of those with total TI and 53% of those on MTI, respectively. Conclusions: In our study, we observed high frequency of the TI in HIV in paediatric HIV clinical practice. All TIs, including 3TC MTI, were associated with significantly lower endpoint median CD4 counts and higher median VLs, as compared to CT in paediatric patients. The high frequency of TI and associated poor outcomes suggest a need for a better strategy in managing the course of the paediatric and adolescent cART.